Small chaperons and autophagy protected neurons from necrotic cell death - Ye Lei (Nature Portfolio, 2017)
Abstract Neuronal necrosis occurs during early phase of ischemic insult. However, our knowledge of neuronal necrosis is still inadequate. To study the mechanism of neuronal necrosis, we previously established a Drosophila genetic model of neuronal necrosis by calcium overloading through expression of a constitutively opened cation channel mutant. Here, we performed further genetic screens and identified a suppressor of neuronal necrosis, CG17259, which encodes a seryl-tRNA synthetase. We found that loss-of-function (LOF) CG17259 activated eIF2α phosphorylation and subsequent up-regulation of chaperons (Hsp26 and Hsp27) and autophagy. Genetically, down-regulation of eIF2α phosphorylation, Hsp26/Hsp27 or autophagy reduced the protective effect of LOF CG17259, indicating they function downstream of CG17259. The protective effect of these protein degradation pathways indicated activation of a toxic protein during neuronal necrosis. Our data indicated that p53 was likely one such protein, because p53 was accumulated in the necrotic neurons and down-regulation of p53 rescued necrosis. In the SH-SY5Y human cells, tunicamycin (TM), a PERK activator, promoted transcription of hsp27; and necrosis induced by glutamate could be rescued by TM, associated with reduced p53 accumulation. In an ischemic stroke model in rats, p53 protein was also increased, and TM treatment could reduce the p53 accumulation and brain damage.